Investigation of Bioimpacts of Metallic and Metallic Oxide Nanostructured Materials: Size, Shape, Chemical Composition, and Surface Functionality: A Review. (31st August 2021) - Fatehbasharzad, Parisa; Fatehbasharzad, Pegah; Sillanpää, Mika; Shamsi, Zahra
Abstract: Nanotechnology is set to impact a wide range of various fields, including medicine, materials technology, environmental sciences, and engineering/manufacturing. Nanoparticles are categorized depending on their size, composition, shape, and surface functionality. Due to the excessive growth of nanostructured materials (NSMs) in production and industrial applications, human and environmental exposure to them and their possible toxicity issues are inevitable. The main objective of this review is to study NSMs, in particular metallic and metallic oxide nanoparticles, and properties that have a determinative role in their bioimpacts. Nevertheless, the main focus is to provide an overview of NSMs toxicology. Medical and environmental applications of the NSMs are discussed here. Also, key factors on the toxicity of the nanoparticles such as shape, size, chemical composition, and surface functionality are discussed. Finally, toxicity of the nanoparticles is going to be highlighted, and relevant studies are critically compared. This review gives a broad scientific view for improving the functional efficiency of nanomaterials while mitigating their possible adverse and unintended effects on biological systems. Abstract : In this review, the application of nanostructured materials (NSMs), especially metallic and metallic oxide nanoparticles, is reviewed comprehensively in two momentous areas, the medical and the environmental field. Toxicity‐related side‐effects of these materials profoundly discuss in this review, and the major factors affecting toxicity like size, shape, composition, and surface functionality of NSMs are propounded.